Ilmu Hukum Vis A Vis Pancasila; Upaya Mewujudkan Substantive Justice - Sri Priyati (Fakultas Hukum Universitas Bhayangkara Surabaya, 2010)
There are various legal problems and have become the centrality of Law discipline analysis with different perceptions and visions. College teaching of law should take account of considering ideology’s value (Pancasila). The current phenomena is a massive reduction of norms causing the emergence of much positive accentuated law by means of subscience influence in defining law as fairly law. Finally, the law has become isolated from non jurisdictionary component which determine the existence of law in society which is ignorant to citizenry need. In colleges law has been taught the law with its ‘justice’, meanwhile the outside law still violates of human right.